PENERAPAN MEDIA PEMBELAJARAN QUIZIZZ PADA ELEMEN UTILITAS BANGUNAN TERHADAP HASIL BELAJAR SISWA KELAS XI KGS DI SMK - Natasya Vania Rahmawati; Hendra Wahyu Cahyaka (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This investigation was engineered to mathematically analyze the variance in students' learning outcomes and map their perceptual responses toward the integration of Quizizz-based instructional media as opposed to conventional PowerPoint (PPT) platforms. The study was anchored on the pedagogical imperative of incorporating interactive digital toolkits to stimulate student engagement and transmute abstract vocational contents into highly consumable and engaging structures. Methodologically, a quantitative paradigm was deployed utilizing a quasi-experimental design. The research subjects were stratified into two distinct observational cohorts within the 11th-grade Building Construction and Sanitation (KGS) department at SMK Negeri 5 Surabaya: the control group operating via PowerPoint frameworks and the experimental group subjected to the Quizizz intervention. Academic performance vectors were synthesized using pretest and posttest instruments, whereas students' psychological acceptance of the respective media was captured through structured questionnaires. The empirical outcomes demonstrate a statistically significant disparity in learning outcomes between the two treatment groups. Numerically, the experimental cohort's mean score expanded from a baseline of 66.3 to 86.6, whereas the control cohort's mean score shifted from 61.4 to 83.2. The inferential t-test calculation yielded a significance coefficient of 0.022 (< 0.05), validating the superior efficacy of the gamified platform over traditional delivery modes. Furthermore, the perceptual matrix indicated that 80% of students' cumulative evaluations regarding Quizizz fell squarely into the